Souhrn aktuálních poznatků v prevenci onemocnění spalničkami; doporučení Advisory Committee on Immunization Practices (ACIP) v kontextu současné epidemiologické situace v ČR - Fabiánová, Kateřina; Manďáková, Zdenka; Lexová, Pavla; Košťálová, Jana; Orlíková, Hana; Špačková, Michaela; Kynčl, Jan; Částková, Jitka; Limberková, Radomíra; Martinková, Irena (Zprávy Centra epidemiologie a mikrobiologie (2011, Print), 2018)
Measles, by their nature, meet the criteria for a disease that can be eliminated or even eradicated worldwide. No animal or environmental reservoir has been known and accurate diagnostic tests are available as well as a highly effective and safe vaccine. Despite the major efforts made to achieve global elimination of measles, the goal has not yet been reached. To achieve herd immunity, a 95 % vaccine coverage rate with two doses is required in accordance with the World Health Organization (WHO). A decline in the overall vaccine coverage rate results in persisting circulation of the measles virus in the population and in an increased number of susceptible individuals. This, in particular, is the reason behind the emergence of recent outbreaks. According to the WHO Regional Verification Commission for Measles and Rubella Elimination, an outbreak is defined as two or more laboratory confirmed cases of measles which are linked in time, epidemiologically, or virologically [1].
Keywords: Vaccination; Česká republika; vakcinace; spalničky; Epidemics; Czech Republic; Measles-Mumps-Rubella Vaccine; Measles; lidé; vakcína proti spalničkám, příušnicím a zarděnkám; Humans; epidemie